Innovation in postgraduate education in communication: service learning as a pedagogical strategy. - Álvarez Nobell, Alejandro; Vadillo Bengoa, Nerea (Historia y Comunicación Social, 2014)
The service-learning proposals APS-applied to graduate in communication, they want to provide more social and practical meaning to academic knowledge and also form social responsibility. This article describes the practice of service-learning training called “Solidarity Marathon Corporate Communication: Protagonists of Change” that in a row, in 2012 and 2013 was held in Zaragoza, sponsored by BrandPR Master in Marketing and Communication Corporate San Jorge University.
Keywords: Communication; Learning Service; ApS; Teaching Innovation; Social Responsibility University; Postgraduate